A Study on Multiple Crew Based Productivity Scheduling Method in Construction Projects - J, Rajprasad; V, Thamilarasu; Lokesh Kumar Reddy, C (International Journal of Engineering and Technology, 2018)
The development construction assumes a critical part in any developing nation. Now a days time, cost and productivity of project had become primary concern of all the construction projects so in order to tackle the time, work and resource productivity in the scheduling works. There is most likely that development is a key movement inside any economy; it impacts, and is affected by, the country's (GDP).The objective to investigation andÂ find out the RII to identify rank of factor to influence multiple crew based productivity scheduling for construction projects on Chennai. To achieve this objective, 30 productivity scheduling factors of multiple crew which are grouped as seven groups: a)design and planning engineer crew ,b).engineering crew, a) construction supervisor crew, d) labour crew, e) fabrication crew, f) safety crew, g)quality crew and this are done by the questionnaire survey and representative by the statistical approach. The factors which effects on multiple crew based productivity schedulingÂ are investigated and top 10 are the most critical factors which are given as follows: (1) Shortage of labours , (2) Shifting methods ,(3)Financial issuesÂ Â ,(4)WorkmanshipÂ , (5) Insufficient lighting ,(6)DistributionÂ of skill labour, (7) Skill of labour,Â (8) Weather conditions, (9) Preparing and assigning the resources ,(10) Length of working day. Despite the fact that the results of this investigation inÂ factors affecting on multiple crew in the construction companies in Chennai to fill a gap of knowledge used by constructionÂ industry members to construct up a more deeper and widerÂ viewpoint of the issues affecting the productivity of crew, and give direction to engineers, managers, experience persons of multiple crew force for effective utilization, consequently help with accomplishing a realistic level of effectiveness and financially effective activity.Â